Abrogasi al-Qur’an dengan Sunah menurut Ibnu Qutaibah dalam Ta’wîl Mukhtalaf al-Hadîts - Abbas Sofwan (Universitas Darussalam Gontor, 2018)
Nasakh or abrogation of the Qur’anic law by the sunna is one of debated subject between ulama. A well-known view on this is that the jumhur ulama reject the view on hadith can abrogate the law of the Qur’an. For the reason the position of the Qur’an is above the hadith. On the contrary of that, we cannot deny that many ulama agreed that hadith or sunna can remove it. This last group expressed their opinion using a strong argument. This debate raised negative things not only for the scholars in person, but also for the teaching of Islam, where some group appeared to insult the the Prophet’s companions, to falsify Prophet’s hadith and deny it. Ibn Qutayba discusses this abrogation in detail in his book Ta’wîl Mukhtalaf Hadîts. Ibn Qutaibah is well-known as an expert in various disciplines of scholarship and Arabic linguistics. In his work, Ibn Qutayba gives an explanation which is supported by historical facts and the hadiths, and proves that the sunnah of the Prophet also has the authority to create, move, regulate, and even remove the law of the Qur’an. With this work Ibn Qutaibah can be the bridge as well as conciliator for the Muslim groups who are in quarrel.